Alcohol Septal Ablation: An Option on the Rise in Hypertrophic Obstructive Cardiomyopathy - Arévalos, Victor (J Clin Med, 2021)
Hypertrophic cardiomyopathy (HCM) can cause symptoms due to the obstruction of the left ventricle outflow tract (LVOT). Although pharmacological therapy is the first step for treating this condition, many patients do not fully respond to the treatment, and an invasive approach is required to manage symptoms. Septal reduction therapies include septal myectomy (SM) and alcohol septal ablation (ASA). ASA consists of a selective infusion of high-grade alcohol into a septal branch supplying the basal interventricular septum to create an iatrogenic infarction with the aim of reducing LVOT obstruction. Currently, SM and ASA have the same level of indication; however, ASA is normally reserved for patients of advanced age, with comorbidities or when the surgical approach is not feasible. Recent data suggests that there are no differences in short- and long-term all-cause mortality, cardiovascular mortality and sudden cardiac death between ASA and SM. Despite the greater experience and refinement of the technique gained in recent years, the most common complication continues to be complete atrio-ventricular block, requiring a permanent pacemaker. Septal reduction therapies should be performed in experienced centres with comprehensive programs.